Sosialisasi Transaksi Digital Kepada Santri Di Yayasan Al-Irfan Jatiluhur Purwakarta - Almuharima, Wina Savana; Erlia, Ega; Jalaludin, Jalaludin (STIE Syariah Indonesia Purwakarta, 2022)
Santri today must be able to balance with the development of the era, one of which is technology, students like it or not must be aware of the emergence of new habits, new ways of communicating via online, lecturing via online, even reciting together can be done online like an online seminar activity. Santri when they enter the community directly will become agents of change, which is expected not only to be agents of change in the field of religion, but various aspects including agents of change in balancing with technological developments. The purpose of the PKM program on Dissemination of Digital Transactions to Santri is to provide an understanding of the current trend of Digital Transactions among students of the Al-Irfan Purwakarta Foundation, and as a way to create santripreneurs. This PKM method uses a lecture and discussion approach. The results of the PKM regarding the socialization of digital marketing to the students of the Al-Irfan Foundation in the village of Mekargalih, Jatiluhur District, Kab. Purwakarta saw that the participants really enjoyed and listened well, because the socialization materials were thoroughly discussed starting from how to use social media, how to sell goods in E-commerce, to discussing material on how to transact on social media. With this digital marketing socialization program, students are able to adapt to the times, so that later students will not only be public figures in the religious field, but all problems of the people can provide solutions. Other PKM support programs include participating in regular Friday night recitation activities and Isra Mi'raj commemorations. These activities create a new atmosphere in the recitation place, and make all the congregation even more enthusiastic about participating in regular recitations.